MENINGKATKAN KEMAMPUAN BERBICARA MELALUI METODE BERMAIN PERAN PADA ANAK USIA 4-5 TAHUN DI PAUD DARUSSA’ADAH DESA TANJUNG BERULAK KECAMATAN KAMPAR KABUPATEN KAMPAR - Yulita, Efni; Zulkifli, Zulkifli; Chairilsyah, Daviq (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Based on field observations of the speech the students do not develop optimally. So that should be the application of methods play a role. This study aims to determine the increase children's ability to talk through methods play a role in children aged 4-5 years in early childhood village Darussa'adah Tanjung Barulak District Kampar regency of Kampar. This research is a type of research that use or classroom action research (PTK) conducted in two cycles. Each cycle consists of planning, action planning, observation / evaluation and reflection. This research subject is a child is a child aged 4-5 years amounted to 15 children. The research data obtained through observation and data analysis were performed quantitatively. The results showed under meted o play a role to improve the speech of children aged 4-5 years. It can be seen from the increase in the average percentage of children's speech on the first cycle of 36.77% which is the criterion undeveloped (BB) and an increase of 36.77% in the second cycle be 57.33% which is at criteria developing according to expectations (BSH). So, methods play a role can improve to speech the student early childhood village Darussa'adah Tanjung Barulak District Kampar regency of KamparKeywords: Speech, Method Acting